STUDY ACADEMIC DISHONESTY STUDENTS - SARI, SITI ARFIATUR ROHMAH (Al Hikmah: Jurnal Tarbiyah dan Ilmu Keguruan, 2022)
government established several policies which are often referred to as student burdens. Despite having the character of encouraging participants to have broad knowledge, in reality students experience boredom in learning and often procrastinate their work because the fatigue they feel begins to make them inconsistent and focused in teaching and learning activities. The possible impact of this phenomenon causes students to believe in their ability to do any given task, so that students will strive for themselves to get good grades even though this behavior is carried out by means of negative actions. One form of deviant action that is often done by students is dishonesty in academics (Academic dishonesty). Academic dishonesty is an act of dishonesty committed by students in obtaining success due to a lack of self-confidence. This research uses quantitative research methods. The quantitative method uses a descriptive quantitative approach, with a population of 361 students, the researcher's sampling technique uses a proportional stratified sampling technique. Because the population in this study has members or elements that are proportionally stratified with a total of 180 students. The instruments and methods used are questionnaires and documentation. The data analysis technique used is descriptive analysis. Based on the results of the research that has been done, the researchers conclude that 76.18Â students who are in the High category. From the number of students 180 students, 0 students / 0% students were in the very low category, 11 students / 6% were in the low category, 63 students / 35% were in the medium category, 70 students / 39% were in the high category and 36 students / 20% of students in the very high category. According to Bernard and Patricia, academic dishonesty has four dimensions, namely cheating, forgery (fibrasi), plagiarism and wrong collaboration.Â